Adolescents' Perceptions of Mother's Career Involvement in Academic Achievement - Syamsuddin, Saphira Salsabilah; Dewi, Eva Meizara Puspita (Polteknik Ilmu Pemasyarakatan, 2023)
This research aims to describe adolescents' perceptions of the dual role of career mothers, the involvement of career mothers in education, and the meaning of career mothers' involvement. Three research subjects met the research criteria, namely Indonesian citizens, aged 12 - 21 years, and had a career mother. The research method used is a qualitative method with a phenomenological approach with data collection techniques using in-depth interview methods. Research findings show that adolescents perceive the dual role of career mothers positively and negatively. The involvement of career mothers in adolescents' education is a form of adolescents' positive perception of career mothers, while negative perceptions are mostly related to lack of communication and togetherness due to mothers' busy schedules. Career mothers are involved in adolescent education through material and emotional support. Research also finds that the effectiveness of implementing the dual role of career mother can also be a factor in adolescents' career choices. The overall research results show that mothers' career involvement in education is perceived as having an influence on adolescents' academic achievement.